PERANCANGAN SISTEM INFORMASI ELECTRONIC NEW STUDENT REGISTRATION STUDI KASUS LEMBAGA BAHASA DAN PENDIDIKAN PROFESIONAL (LBPP) LIA PRAMUKA JAKARTA - Tri Hartati (JURNAL TEKNIK INFORMATIKA, 2019)
The rapid development of information technology can meet a variety of human activities and needs, the use of computers can provide the effectiveness of a good life for humans, besides that with a computer someone is able to create a useful technological system. Today's internet technology has the privilege of finding information in other parts of the world without being hindered by distance, time and place. Based on the background stated above, with this the author tries to design a new student registration website, so that it can partially replace the role of the new student registration officer. The design of this web application will provide many conveniences in the process of registering new students, especially for students or parents who have a busy schedule so that registration of prospective students can be done online. This system provides an information that is registration activities for prospective new students, LIA profiles, verification and announcements of level placement at the Institute of Language and Professional Education (LBPP) LIA Pramuka Jakarta.